Pilgrimage, Tradition, and Social Status: The Ritual of Hajj as an Identity for Moslems Community in Gresik - Muawanah, Siti; Mustolehudin, Mustolehudin (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Hajj is a hard worship for the Moslems because it requires three abilities at the same time: physical ability, mental ability, and ﬁnancial ability. Consequently, not all people are able to perform the hajj. Furthermore, hajj is a very long process of worship and, therefore, has given birth to numerous traditions from the departure until the arrival from the holy land. In line with the phenomena of hajj, especially in the context of Gresik East Java Indonesia, this study strives to explore how the tradition of hajj is performed. By using qualitative method, this research found some important ﬁndings. First, there are various traditions conducted by people of Gresik in terms of performing hajj: pamitan haji, sejarah haji, walimatussafar, dulkadiran, nuzulan, khatmil Qur’an, and tasyakuran. These traditions are performed because they are considered important especially for those who will embark on their hajj journey. Second, from the socio-economic perspective, the performance of hajj traditions can result in social discrepancy for the lower middle-class people. The implication is that for the people of Gresik who have only been able to aﬀ ord the cost of the hajj journey, then the cost of the hajj traditions can be a peculiar morale burden because the cost of the hajj traditions is equal to the personal cost of the hajj journey.